TO STUDY THE EFFECT OF SNAKE GOURD, REETHA AND SHIKA KAI HERBAL ANTI-DANDRUFF SHAMPOO AND COMPARISON WITH MARKETED SHAMPOOS - VISHAL, KULKARNI; PRASHANT L, PINGALE (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Reetha and shika kai possess the anti-dandruff activity; the present study involves studying the effect of reetha, shika kai and snake gourd on the anti-dandruff activity. This work reveals the potency of each herbs anti-dandruff activity and it change in anti-dandruff action when they are used in combination with each other in a different concentration. These works conclude, in the formulation of good anti-dandruff shampoo, does individual herbs are enough to formulate shampoo or are there necessary to be use the herbs in a combination to get better effect. In the present study effort also taken to compare the formulated preparation with the marketed preparation, so as to get an idea about impact of herbs anti-dandruff activity. Already many scientific study reveals that, usage of alkalonamides in many synthetic shampoos are the carcinogenic and have some side-effects so, in the present work effort has been taken to eliminate alknolanamide containing ingredients to formulate the natural anti-dandruff shampoo. Keywords: Anti-dandruff, Reetha, Shika kai, Snake gourd.